2019
DOI: 10.1530/rep-18-0633
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of the placental renin–angiotensin system in human fetal growth restriction

Abstract: Fetal growth restriction (FGR) is a pregnancy complication wherein the foetus fails to reach its growth potential. The renin–angiotensin system (RAS) is a critical regulator of placental function, controlling trophoblast proliferation, angiogenesis and blood flow. The RAS significantly influences uteroplacental blood flow through the balance of its vasoconstrictive and vasodilatory pathways. Although the RAS is known to be dysregulated in placentae from women with preeclampsia, the expression of the RAS has no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 39 publications
1
29
0
1
Order By: Relevance
“…Indeed, ACE2 metabolizes Ang II and reduces its levels and produces the vasodilator peptide, Ang-(1-7). Therefore, it is critical for regulating the actions of Ang II mediated by its AT 1 R. A previous study from our group showed that placental ACE2 mRNA expression was lower in pregnancies associated with fetal growth restriction (Delforce et al, 2019), suggesting that reduced placental ACE2 levels and reduced Ang-(1-7) production might contribute to the etiology of SGA. The elevation in plasma ACE2 levels in SGA, taken together with the reduction in placental ACE2, suggests, however, that placental ACE2 is not contributing to the high levels of sACE2 in the maternal circulation in SGA pregnancies.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Indeed, ACE2 metabolizes Ang II and reduces its levels and produces the vasodilator peptide, Ang-(1-7). Therefore, it is critical for regulating the actions of Ang II mediated by its AT 1 R. A previous study from our group showed that placental ACE2 mRNA expression was lower in pregnancies associated with fetal growth restriction (Delforce et al, 2019), suggesting that reduced placental ACE2 levels and reduced Ang-(1-7) production might contribute to the etiology of SGA. The elevation in plasma ACE2 levels in SGA, taken together with the reduction in placental ACE2, suggests, however, that placental ACE2 is not contributing to the high levels of sACE2 in the maternal circulation in SGA pregnancies.…”
Section: Discussionmentioning
confidence: 86%
“…It is activated by estrogen-induced increases in angiotensinogen (AGT) and, subsequently, by the reduction in systemic vascular resistance caused by the ovarian hormone, relaxin (Lumbers and Pringle, 2014). It is perhaps not surprising then that alterations in the circulating and intrauterine RAS are associated with the development of preeclampsia (PE) and pregnancies in which the infant is born small for gestational age (SGA) (Irani and Xia, 2008;Zhou et al, 2013;Delforce et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, enhanced cerebral perfusion occurs at the expense of fetal liver, renal, pancreatic and mesenteric circulation, which in turn results in decreased production of insulin growth factor, angiotensin and other endocrine hormones essential for fetal growth (22). These hormones may affect the fetal growth directly as is the case of insulin growth factor or indirectly via placental function (e.g., renin-angiotensin system), inducing an inflammatory response or through other biomolecular pathways (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…180,181 These drugs modifying the reninangiotensin cascade could also affect placental functions leading to growth retardation. 182 Other drugs with vascular impact Sildenafil, a phosphodiesterase type 5 inhibitor, is a vasodilator used to treat erectile dysfunction and pulmonary arterial hypertension. It is under investigation in patients with COVID-19 (NCT04304313) because pulmonary hypertension is a complication of ARDS.…”
Section: Immune Modulatorsmentioning
confidence: 99%